Clinical characteristics and factors associated with acute kidney injury among patients hospitalized with coronavirus disease: an observational retrospective study - Dehesa-López, Edgar; Galindo, Adolfo Entzana; Santos, Irali María Velasco; Aros-Pérez, Michel Alberto; Rodríguez, Diego Manuel Gómez; Ojeda-Mendoza, Erick; Ide, Brenda Paola Aguilar (São Paulo Medical Journal, 2022)
BACKGROUND: Coronavirus disease 19 (COVID-19) is a multisystemic disease with high incidence of acute kidney injury (AKI). OBJECTIVE: To describe the clinical characteristics and factors associated with AKI among patients hospitalized with COVID-19. DESIGN AND SETTING: Retrospective cohort conducted at Hospital Civil de Culiacan, Mexico. METHODS: We included 307 patients hospitalized due to COVID-19. AKI was defined and staged based on serum creatinine levels in accordance with the criteria of the Acute Kidney Injury Network (AKIN). Multivariate logistic regression analysis was used to determine factors associated with AKI. RESULTS: The patients’ age was 56 ± 15 years (64.5% male). The incidence of AKI was 33.6% (n = 103). Overall, 53.4% of patients had community-acquired AKI, and 46.6% had hospital-acquired AKI. Additionally, 15.5% of them presented AKIN stage 1; 34% had AKIN stage 2; and 50.5% had AKIN stage 3. Hemodialysis was required for 10.7% of the patients. the factors associated with AKI were chronic kidney disease (odds ratio, OR: 10.8; P = 0.04), use of norepinephrine (OR: 7.3; P = 0.002), diabetes mellitus (OR: 2.9; P = 0.03), C-reactive protein level (OR: 1.005; P = 0.01) and COVID-19 severity index based on chest tomography (OR: 1.09; statistical trend, P = 0.07). Hospital stay (11 ± 7 days; P < 0.001) and mortality (83.5 versus 31.4%; P < 0.05) were greater among patients with AKI. CONCLUSION: AKI was a frequent and serious complication in our cohort of patients hospitalized with COVID-19, which was associated with high mortality and long hospital stay.